Rethinking on Research on Science Popularization Theory in China - Qi, Peixiao (Advances in Social Sciences Research Journal, 2021)
Science popularization research serves as a fundamental role in the work of science popularization, which requires the guidance of the theory. The research on science popularization is a process to explore and understand laws of science popularization work, and also the rational thinking and summary of science communication experience. Based on the description of China’s studies on science popularization theories, three fundamental problems in China’s modern science popularization theory are given priority to discussion and some relevant reflections about further development are proposed.